Flower power: testing social media advertising strategies for floral products - Rachel Corry; William R Taylor; Jessica Holt; Hailey Bittles; Benjamin L. Campbell; Julie Campbell (Journal of Applied Communications, 2023)
Social media and the internet have impacted how companies and organizations advertise to consumers. Digital advertising has created the opportunity to engage with consumers, target specific groups, and capture metrics of use to help build effective advertising strategies. The floral industry is a large sector within the agricultural arena, which is primed to engage with young consumers. This research examined the effectiveness of utilizing static and animated social media advertisements to increase consumers’ intention to purchase floral products. Using an online survey and an experimental design, this study examined 8,488 respondents’ intention to purchase floral products after viewing static and animated social media advertisements. This study identified respondents’ attitudes, social norms, age, and internet use to be significant predictors in their intent to purchase floral products. Recommendations from a theoretical and applied perspective are discussed within relation to the study’s findings to advance strategic advertising in the floral industry.
Keywords: social media advertising; animated advertisements; floral industry advertising; strategic advertising